FINANCIAL PERFORMANCE ANALYSIS OF CONVENTIONAL AND SHARIA BANKS (Studies in the Form of state-owned Bank ) - Yuhansyah, Dio Sasta; Ludigdo, Unti (Jurnal Ilmiah Mahasiswa FEB, 2013)
This  study  aims  to  analyze  how  the  performance  of  State-Owned  Sharia  Bank compared to State-Owned Conventional Bank. It also aims to analyze the alternative of State-Owned Sharia Bank establishment. Indicators of bank performance assessment are based on bank health assessment which assessed  through capital, asset quality, management, earning, liquidity. The population  in  this study  is State-Owned Bank which will be  the main candidate for establishment of State-Owned Sharia Bank, both the conventional and sharia entities with total 6 (six) banks, namely  : PT. Bank Rakyat  Indonesia, Persero  (Tbk), PT. Bank Mandiri, Persero (Tbk), PT. Bank Nasional Indonesia, Persero (Tbk), PT. Bank BRI Syariah, Persero, PT. Bank Syariah Mandiri, Persero, PT. Bank BNI Syariah, Persero. This research was conducted using analysis of comparative data that is comparing one data with the other's data. CAMEL variables which used to analyze the health rate of the bank of 8  (eight)  ratios,  that are  : capital adequacy  ratio  (CAR), non performing  loan  (NPL), net profit margin  (NPM),  return  on  asset  (ROA),  return  on  equity  (ROE),  net  interest margin (NIM), operating expense to operating income (BOPO), and loan to deposit ratio (LDR). The type of data used is quantitive data in the form of annual reports of banks during the period of 2010-2012. The  results  of  this  study  indicate  that  conventional  banks  have  better  performance than Sharia Banks.  In addition, alternative establishment of  state-owned Sharia Banks wich reflect better performance is by merging Sharia and Conventional entities that exist under the same bank. Keywords: performance, State-Owned Sharia Bank, CAMEL (capital, asset, management, earning, liquidity), CAR, NPL, NPM, ROA, ROE, NIM, BOPO, LDR, comparative